Exploring the interface of relationship marketing and export performance: A conceptual perspective. Issue 2 (16th December 2019) - Hasaballah, Abdel Hafiez Ali; Genc, Omer Faruk; Mohamad, Osman Bin; Ahmed, Zafar U.
Abstract : Purpose: The purpose of this study is to develop a comprehensive model that explains the influence of different relational variables on export performance and the interaction between those relational variables. Design/methodology/approach: This is a theoretical paper building upon the relational variables and export performance literatures. Findings: A theoretical model was developed based on the existing studies and findings. In the proposed model, relational outcome variables mediate the effect of relational contextual variables on export performance. Research limitations/implications: The model developed in this study opens new avenues for future research because it provides a different perspective on how relational variables interact with each other in terms of their impact on export performance. Practical implications: Relational variables have great importance for firms' export performance. This study provides a framework about how these variables affect export performance, which should be taken into consideration in firms' strategies and decisions with regard to the relations with partners. Originality/value: Despite the consensus about the importance of relational variables, the evidence is mixed with regard to the way they affect export performance. With the proposed model, this study aims to fill this gap by providing a framework that explains how relational variables interact with each other and how they affect export performance.